Deep Learning-Based COVID-19 Diagnostics of Low-Quality CT Images - Ferber, Daniel; Vieira, Felipe; Dalben, João; Ferraz, Mariana; Sato, Nicholas; Oliveira, Gabriel; Padilha, Rafael; Dias, Zanoni (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2021)
Mass testing of the population is among the most effective measures to combat the COVID-19 pandemic. Among existing diagnostic methods, deep learning-based solutions have the potential to be affordable, quick and accurate. However, these techniques often rely on high-quality datasets, which are not always available in medical scenarios. In this work, we use convolutional neural networks to diagnose COVID-19 on computed tomography images from the COVIDx-CT dataset. The available scans often present noisy artifacts, originated from sensor- and capturing-related errors, that can negatively impact the performance of the model if left untreated. In this sense, we explore several preprocessing strategies to reduce their impact and obtain a more accurate method. Our best model, a ResNet50 fine-tuned with preprocessed images, obtained 97.84% accuracy when prompted with a single image and 99.50% when processing multiple images from the same patient. In addition to achieving high accuracy, interpretability experiments show that the network correctly learned features from the lung and chest area.